Single crystal growth of Ga3Ni2 by the Czochralski method - Wencka, M (2016)
The authors are grateful to Stefanie Hoser for surface polishing of the samples. This work has been partly conducted within the European integrated Center for the development of new Metallic Alloys and Compounds (European C-MAC). M.W. and M.P. are grateful for funding by the German Academic Exchange Service (DAAD), Grant no. A/14/02942, and by Peruvian Council of Science and Technology (CONCYTEC), Grant no. 221-2014-FONDECYT, respectively.